Efek Komposisi Beberapa Media Tanam Terhadap Pertumbuhan dan Produksi Tanaman Mentimun (Cucumis sativus L.) - Muhammad Irfan; Badrul Ainy Dalimunthe; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2022)
One of the factors that influence growth and yield of cucumber is growing media fertility. Fertility of growing media can be increased by the composition of several growing media, through the use of planting media such as solid, manure, sand, soil. expected to increase growth and yield of cucumber plants. The study was carried out on the Labuhanbatu Stiper experiment area located on Jl Manunggal Amd Bakaran Batu Rantau Selatan Kab. Labuhanbatu North Sumatra. Starting from December 2018 to completion. The study was conducted using Non Factorial Randomized Block Design (RBD) with 1 planting media treatment factor, namely by using the composition of several planting media with 8 treatments (P0: Soil (control), P1: Solid + Soil (1: 3), P2: Fertilizer Cage + Land (1: 3), P3: Land + Sand (3: 1), P4: Land + Solid + Manure (2: 1: 1), P5: Land + Solid + Sand (2: 1: 1), P6: Soil + Manure + Sand (2: 1: 1), P7: Soil + Solid + Manure + Sand (1: 1: 1: 1) The observed parameters are plant length, stem diameter, number of leaves, and fruit weight The results of this study indicate that the utilization of several planting media compositions in treatment P5 affects the parameters of plant length, stem diameter, number of leaves, fruit weight. Keywords : planting medium composition, production and growth, cucumber